Pulmonary Disease in Beta-Thalassemia - S. Theodoropoulos, Demetrios; S. Theodoropoulou, Maria (Current Respiratory Medicine Reviews, 2016)
The care of beta-thalassemia has improved dramatically over the last few decades mostly because of: i) improved blood transfusion regimens; ii) wide-spread use of deferoxamine; iii) surgical advances; and iv) allogeneic hematopoietic stem cell transplantation. Advanced healthcare standards, improved life expectancy, and complications specific to beta-thalassemia necessitate a renewed approach to the pulmonary issues of this disease. While transfusion-related infections are expected, and Streptococcal, Staphylococcal, E. coli and Salmonella infections are common, a number of special problems are also reported. Mycoplasma pneumoniae infections associated with hemolytic anemia, Pneumocystis carinii pneumonia and necrotizing pneumonia caused by Klebsiella pneumoniae are indicative of the special susceptibility to infections in beta-thalassemia. The issue of immune function in the (non-transplanted) patient with thalassemia is brought up. Conditions associated with chronic airway inflammation, such as plastic bronchitis and allergic bronchopulmonary mycosis, are discussed as well as life-threatening complications. In an attempt to organize the diagnostic approach to pulmonary disease in beta-thalassemia, four working entities are delineated, which, almost invariably, tend to overlap and aggravate each other: i) disorders inherent to the beta-thalassemia hemoglobinopathy; ii) chronic lung disease and its complications; iii) immunological corollaries of the therapy of beta-thalassemia, i.e. chronic transfusion, splenectomy and bone marrow transplantation; and iv) airway inflammation.
Keywords: tranfusion